2013
DOI: 10.21273/hortsci.48.9.1159
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Ex Vitro Rooting and Acclimatization Method for Horticultural Plants Using Float Hydroculture

Abstract: This article presents a new acclimatization method, ex vitro acclimatization in float hydroculture. This protocol ensures the ex vitro acclimatization of the plantlets obtained in vitro in the rooting stage or the ex vitro rooting and acclimatization of the shoots obtained in the multiplication stage. Our hydroculture method is different from the techniques of flotation hydroculture because no fertilizers or plant growth regulators or other biostimulators are used and water oxygenation by bubbling is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 5 publications
1
14
0
1
Order By: Relevance
“…Gonzalez et al proposed a mixture of peat and perlite (1:1, v/v) for hardening of blackberry, blueberry and raspberry, and 100% of rooted plants were adapted . Direct ex vitro rooting in floating perlite was successfully applied in tayberry plants, with78.12% rooting . In our study, the micropropagated tayberry plants and adapted under field conditions did not exhibit any morphological variations when compared with mother plants, and gave a large number of fruits.…”
Section: Discussionsupporting
confidence: 46%
“…Gonzalez et al proposed a mixture of peat and perlite (1:1, v/v) for hardening of blackberry, blueberry and raspberry, and 100% of rooted plants were adapted . Direct ex vitro rooting in floating perlite was successfully applied in tayberry plants, with78.12% rooting . In our study, the micropropagated tayberry plants and adapted under field conditions did not exhibit any morphological variations when compared with mother plants, and gave a large number of fruits.…”
Section: Discussionsupporting
confidence: 46%
“…For the ex vitro acclimatization of plantlets rooted in vitro we recommend the use of floatation hydroculture due to its simplicity and reliability and due to the very high survival percentage obtained. This technique was developed at the Fruit Research Station Cluj (Clapa et al, 2013) and is effective for several species. It was inspired from float hydroponics, a very simple and effective hydroponic technique (Reed, 2009;Ross and Teffeau, 1995;Tyson, 1999).…”
Section: Direct Ex Vitro Rooting and Acclimatization Of Shoots Obtainmentioning
confidence: 99%
“…The 'Gisela 5' sweet cherry rootstock is propagated with greenwood, soft or hardwood cuttings (Exadaktylou et al 2009), but also micropropagation has been reported (Ružić et al 2000;Nacheva & Gercheva 2009;Bošnjak et al 2012;Clapa et al 2013;Šiško 2011. An efficiency in tissue culture propagation is strongly influenced by a mineral composition of culture medium and its interaction with other medium compounds, as water quality, sugars, growth regulators, vitamins, etc.…”
Section: Introductionmentioning
confidence: 99%